Hypersexuality and Impulsivity in Self-Referred Men With Sexual Interest in Minors: Are They Related? Do They Change During Treatment? An Exploratory Pilot Study. Issue 5 (9th September 2021) - Lampalzer, Ute; Tozdan, Safiye; von Franqué, Fritjof; Briken, Peer
Abstract: Introduction: Studies on characteristics of self-referred men with sexual interest in minors (SIM) and treatment approaches in this group of patients are still relatively rare. Aim: The aim of this exploratory pilot study was to investigate hypersexuality and impulsivity as 2 dynamic risk factors that could possibly change during treatment in self-referred men with SIM. Methods: Data were collected at the "Kein Täter Werden (means: not become an offender)" network site in Hamburg. Using self-report questionnaires, the extent of hypersexuality and impulsivity was analyzed with the samples' pretreatment data via descriptive statistics and compared with nonclinical samples of other studies. The relation between hypersexuality and impulsivity was analyzed via Spearman's correlation coefficient with pretreatment data ( N  = 77). Intragroup analysis compared hypersexuality and impulsivity from pre- and posttreatment ( n  = 29). Main Outcome Measures: Hypersexual Behavior Inventory and Barratt Impulsiveness Scale Version 11. Results: The degree of generalized impulsivity in the SIM group was comparable to that in nonclinical samples while the degree of hypersexuality was considerably higher than in nonclinical samples. Sixty-four percent of the participants were in the range of clinically relevant hypersexuality. Impulsivity and hypersexuality were weakly positively correlated with each other. During treatment hypersexuality significantly decreased while impulsivity did not differ significantly between before beginning treatment and after (partial) completion. Conclusion: Hypersexuality, but not impulsivity, was pronounced in the group of self-referred men with SIM and should be targeted in treatment. In order to improve treatment outcome regarding risk reduction in self-referred men with SIM, a focus on treatment approaches that were developed to treat hypersexuality can be expected to be effective while focusing on generalized impulsivity may be less relevant.